2022
DOI: 10.31410/balkans.jetss.2022.5.2.115-124
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Capacities as the Key to Survival – A Case Study in Serbia

Abstract: The innovation of companies is of vital importance because it allows them to penetrate markets and provides better connections with emerging markets, which can lead to greater opportunities. Measuring innovation is an important activity both for theoretical and practical tests. This paper presents research on the innovation capacities of small and medium enterprises in Serbia according to the model consisting of 21 dimensions. The observed sample consists of 106 companies, of different sizes, whose activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Indeed, if a company is highly competitive in the market, it is very likely to have a well-developed innovation management system with standards that are largely aligned with European standards. The previous research results have shown that, when it comes to innovation capacity, there are differences between Serbian companies (Vučetić & Kirin, 2022). Various methodologies exist for assessing companies' innovation capacities, and for the purpose of researching the interdependence between sustainability in women-owned small and medium enterprises in Serbia and innovation, a questionnaire was constructed based on a combination of two commonly applied methodologies for assessing innovation potential: the IMP³rove methodology and the Innovate methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, if a company is highly competitive in the market, it is very likely to have a well-developed innovation management system with standards that are largely aligned with European standards. The previous research results have shown that, when it comes to innovation capacity, there are differences between Serbian companies (Vučetić & Kirin, 2022). Various methodologies exist for assessing companies' innovation capacities, and for the purpose of researching the interdependence between sustainability in women-owned small and medium enterprises in Serbia and innovation, a questionnaire was constructed based on a combination of two commonly applied methodologies for assessing innovation potential: the IMP³rove methodology and the Innovate methodology.…”
Section: Introductionmentioning
confidence: 99%